Remembering Marielle Franco as a Martyr? Power and Perils of Martyr-Making as a Strategy to Process Political Suffering - Merian, Katharina (International journal of public theology, 2025)
This article explores the construction of martyrdom surrounding Marielle Franco, a Brazilian human rights activist and Rio de Janeiro city councilor assassinated on 14 March 2018. Using an historical and discourse-analytical approach, it treats martyrdom as a contested phenomenon at the intersection of religion and politics, where meaning evolves as power dynamics shift. Critically engaging with a speech by pastor Henrique Vieira, the study argues that early efforts to frame her assassination as martyrdom, drawing on liberation theology, served as a means of processing political trauma and reinforcing struggles for human rights and social justice. At the same time, this portrayal was challenged by members of Franco’s inner circle, underscoring the potential risks and limitations of labeling political figures as martyrs. The article critically examines both the empowering and problematic dimensions of martyrdom for marginalized communities and social movements, highlighting its complex role as a political and symbolic strategy.